Research trends and hotspots of breast cancer management during the COVID-19 pandemic: A bibliometric analysis - Lyu, Peng-fei; Li, Jing-tai; Deng, Tang; Lin, Guang-Xun; Fan, Ping-ming; Cao, Xu-Chen (Frontiers in Oncology, 2022)
Background: The 2019 COVID-19 disease (COVID-19) pandemic has disrupted people's daily lives, including cancer patients. This study summarizes the current hotspots of Breast Cancer Management during COVID-19 pandemic (BCMP) research and evaluates the BCMP research trends, both qualitatively and quantitatively. Methods: The Web of Science database（WOS） obtained scientific publications of BCMP-related studies from January 1, 2020, to April 1, 2022. Used the BICOMB software to obtain the high-frequency matrix keywords, applying Gcluto software to perform a clustering analysis on the keyword matrix of the paper. The co-occurrence and collaboration analysis between countries, institutions, journals, authors, and keywords were utilized by R language, VOSviewer or CiteScape software. Results: A total of 182 articles related to BCMP were identified. The most productive country and institutions in the BCMP field were the USA and the University of Rome Tor Vergata. BREAST CANCER RESEARCH AND TREATMENT, BREAST, the IN VIVO were the first three periodicals with leading publications in BCMP research. Buonomo OC was the most prolific author in this field, publishing nine articles (9/182, 4.94%), similar to Vanni G and Matarazzo M, cited more than 30 times (h-index (6)). Furthermore, most of the top 10 most cited articles are from Italy (with four articles) and the U.K. (with three articles). According to the co-keywords analysis of BCMP, the top ten hotspots and trends in research are screening, surgery, rehabilitation, emotional, diagnostic, treatment, and vaccine management of breast cancer in the context of the epidemic. The hotspots words were divided into five clusters: Screening for breast cancer patients during the epidemic, Breast cancer surgery during the pandemic, recovery of breast cancer patients during the epidemic, Motion impact of the outbreak on breast cancer patients, diagnosis and treatment of breast cancer patients during the epidemic and vaccination management for breast cancer patients during an epidemic. Conclusion: BCMP has attracted the attention of scholars in many countries in the last three years. The current study revealed significant contributions to BCMP research by country, institution, scholar, and hot research trends.